Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1074/jbc.m112.399790
|View full text |Cite|
|
Sign up to set email alerts
|

An Advanced Glycation End Product (AGE)-Receptor for AGEs (RAGE) Axis Restores Adipogenic Potential of Senescent Preadipocytes through Modulation of p53 Protein Function

Abstract: Background:The impaired adipogenic potential is a hallmark of preadipocyte senescence. Results: Senescent preadipocytes treated with advanced glycation end products (AGEs) resumed adipogenesis in vitro and ex vivo. Conclusion: AGE-induced expression of the receptor for AGEs (RAGE) and AGE-RAGE-dependent inhibition of p53 function restore adipogenesis in senescent preadipocytes. Significance: Glycated proteins could participate in aging-impaired adipose development.The impaired adipogenic potential of senescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 67 publications
(74 reference statements)
0
23
0
Order By: Relevance
“…It is unknown whether this discrepancy was due to different study populations in terms of age, sex, or chronic disease status. Several recent studies examined the involvement of the AGEs/RAGE axis in adiposity [46,55,56]. An animal study showed that CML-AGE accumulation in conjunction with increased expression of RAGE in adipose tissue contributes to the dysregulation of adipokines in obesity and insulin resistance [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether this discrepancy was due to different study populations in terms of age, sex, or chronic disease status. Several recent studies examined the involvement of the AGEs/RAGE axis in adiposity [46,55,56]. An animal study showed that CML-AGE accumulation in conjunction with increased expression of RAGE in adipose tissue contributes to the dysregulation of adipokines in obesity and insulin resistance [16].…”
Section: Discussionmentioning
confidence: 99%
“…The mouse gene primer sequences used for PCR were: mRAGE, forward 5′-AAC ACA GCC CCC ATC CAA-3′, and reverse, 5′-GCT CAA CCA ACA GCT GAA TGC-3′ [14]; mICAM-1, forward 5′-CGC TGT GCT TTG AGA ACT GTG-3′ and reverse 5′-ATA CAC GGT GAT GGT AGC GGA-3′ [15]; mMCP-1, forward 5′-CTG AAG CCA GCT CTC TCT TCC T-3′ and reverse 5′-CAG GCC CAG AAG CAT GAC A-3′ [16] and mGAPDH, forward 5′-CAT GGC CTT CCG TGT TCC TA-3′and reverse 5′-GCG GCA CGT CAG ATC CA-3′ [17]. All samples were measured in triplicates for statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a recent study showed that AGEs augmented the expression of the prothrombotic/inflammatory regulator, plasminogen activator inhibitor-1, in rat white adipocytes, by a ROS-dependent pathway [ 56 ]. Moreover, glycated BSA increased the adipogenic potential of senescent preadipocytes ( in vitro and ex vivo ) via the AGEs-RAGE axis together with an impairment of p53 function [ 57 ]. Here this occurs by direct binding of RAGE to cytosolic p53 together with the AGEs-RAGE suppression of p53 transcript levels.…”
Section: Ages Adipocyte Interactions and The Onset Of Pathologiesmentioning
confidence: 99%